Restorative proctocolectomy for familial adenomatous polyposis coexisting with colorectal cancer - Cüneyt KAYAALP,; Sevil IŞIK,; Soner AKBABA,; Gürel NEŞŞAR,; Erkan OYMACI,; Canbek SEVEN, (Turkish Journal of Gastroenterology, 2019)
-